2007
DOI: 10.1111/j.1471-0528.2006.01216.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of insulin glargine during pregnancy: a case–control pilot study

Abstract: Objective To determine whether the use of insulin glargine during pregnancy is associated with an increase in the incidence of fetal macrosomia or adverse neonatal outcome.Design A matched case-control study.Setting Women's Centre, John Radcliffe Hospital, Oxford, UK.Sample Sixty-four pregnant women treated with insulin during their pregnancies, 20 with type I diabetes and 44 with gestational diabetes.Methods Two groups of women were compared in matched pairs. A study group of 32 pregnant women with diabetes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
1
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 14 publications
2
52
1
7
Order By: Relevance
“…Birth weight and rate of congenital abnormalities were similar. Overall incidence of macrosomia was similar: 37.5% in glargine group and 40.6% in control group (p>0.05) [47].…”
Section: Long Acting Insulin Analoguesmentioning
confidence: 66%
See 2 more Smart Citations
“…Birth weight and rate of congenital abnormalities were similar. Overall incidence of macrosomia was similar: 37.5% in glargine group and 40.6% in control group (p>0.05) [47].…”
Section: Long Acting Insulin Analoguesmentioning
confidence: 66%
“…A statistically significant improvement of mean A1c change from T1 to T3 was demonstrated by Poyhonen-Alho et al [48]. All studies reviewed, reported either no difference in the rate of maternal hypoglycemia or a significantly decreased rate compared to NPH [15,[46][47][48]50,52,53].…”
Section: Glarginementioning
confidence: 88%
See 1 more Smart Citation
“…We read with interest the article by Price et al 1 In their pilot study, Price et al investigated the use of glargine in pregnant women with type I diabetes and gestational diabetes. 1 There are concerns regarding the use of glargine in pregnancy due in part to an increase in insulin-like growth factor-I (IGF-I) receptor affinity (which the authors mention) but also to its mitogenic potency in a cell culture model that used human osteosarcoma cells 2 (which the authors does not mention).…”
Section: Sirmentioning
confidence: 99%
“…1 There are concerns regarding the use of glargine in pregnancy due in part to an increase in insulin-like growth factor-I (IGF-I) receptor affinity (which the authors mention) but also to its mitogenic potency in a cell culture model that used human osteosarcoma cells 2 (which the authors does not mention). IGF-I has been also implicated in the development of mammary, bone and ovarian tumours and in the development of retinopathy.…”
Section: Sirmentioning
confidence: 99%